Attitudes towards English as a Medium of Instruction in Malawian Universities. Issue 1 (2nd January 2019) - Reilly, Colin
Abstract: Malawi's language-in-education policies have been through numerous changes since the colonial period. In 1996 a policy directive was announced which encouraged the use of mother tongues in the early stages of education before transitioning to English. However, this policy was never effectively implemented and, in 2014, an English-only policy was announced. This has resulted in renewed debate on which languages are suitable for use as mediums of instruction in the country. This article will discuss the Malawian language-in-education policy context with a focus on university education, and the prevailing attitudes which students and staff exhibit towards English. This will be done through an analysis of data collected from focal groups and interviews with students and staff in Malawian universities. Results show that while English is viewed positively and as suitable for use within universities it is not viewed uncritically and there are complex attitudes towards the language. English skills are viewed as a valuable resource; however, so too are multilingual language skills. Students and staff also display positive attitudes towards the use of a multilingual language policy in the university suggesting that the recent policy changes in Malawi do not reflect stakeholder attitudes.